1995
DOI: 10.2105/ajph.85.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Changes in adult cigarette smoking in the Minnesota Heart Health Program.

Abstract: OBJECTIVES. The Minnesota Heart Health Program was a research and demonstration project designed to reduce risk factors for heart disease in whole communities. This paper describes smoking-specific interventions and outcomes. METHODS. Three pairs of matched communities were included in the study. After baseline surveys, one community in each pair received a 5-year education program, while both cross-sectional and cohort surveys continued in all sites. Adult education programs for smoking cessation included Qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…A ran dom sample of residents surveyed before the start of the education program was resurveyed. For long-term smoking cessation, the cross-sectional survey data provided evidence of an intervention effect for women but not for men; no such effect was observed for ei ther sex in the cohort sample Lando et al 1995). Unexpectedly, large declines in smoking prevalence, especially among men, were ob served in comparison communities.…”
Section: Reducing Tobacco Usementioning
confidence: 82%
See 2 more Smart Citations
“…A ran dom sample of residents surveyed before the start of the education program was resurveyed. For long-term smoking cessation, the cross-sectional survey data provided evidence of an intervention effect for women but not for men; no such effect was observed for ei ther sex in the cohort sample Lando et al 1995). Unexpectedly, large declines in smoking prevalence, especially among men, were ob served in comparison communities.…”
Section: Reducing Tobacco Usementioning
confidence: 82%
“…A meta-analysis of 62 studies comparing components of behavioral controls found that motiva tional rewards (contingency contracting) did not sig nificantly alter long-term cessation rates (Fiore et al 2000). In the final results of the Minnesota Heart Health Program, the failure of community education methods (which included motivational rewards for smoking cessation) to produce results that exceeded secular trends is an important demonstration of the difficulties in evaluating such modalities (Lando et al 1995).…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier trials, such as the North Karelia Project, 1 the Stanford Three-City Project, 2 and the Swiss National Research Program, 3 cigarette consumption or the prevalence of smoking was reduced. In more recent trials, such as the Stanford Five-City Project, 4 the Minnesota Heart Health Program, 5 the Pawtucket Heart Health Program, 6 and the Heart to Heart Project, 7 results were mixed, with some showing intervention effects on smoking behavior 4,5 but not others. 6,7 Several community trials have specifically addressed smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, individuals who may be isolated from one channel of information (e.g., by low literacy) may be reached by another.5 14 Unfortunately, results of several large community programs have been limited '5 or disappointing. 16 (Table 4). We also examined results separately for subgroups defined by and adjusted for education, income, and employment, variables that several analyses2 have indicated are primarily responsible for manifest differences in smoking between African Americans and Whites.…”
mentioning
confidence: 99%